Testing the suitability of the ACCOM tool to measure outcomes of care for Culturally and Linguistically Diverse older people. Issue 4 (1st October 2020) - Cardona, Beatriz; Mylonas, Christina; Fine, Michael
ABSTRACT: The Australian Community Outcomes Measurement (ACCOM) uses a standardized set of instruments to measures functional, health, and social care-related quality of life (SCRQoL) among older people receiving services at home. One of its key components is the use of modified ASCOT SCT4 survey developed by The University of Kent PSSRU. This paper presents the preliminary findings of a pilot testing of ACCOM with CALD clients in South West Sydney using face to face interviews conducted by bilingual workers as a novel approach to administering the tool. The paper will argue that some of the domains in ASCOT SCT4 survey pose unique challenges for culturally diverse groups that highlight the ethnocentric nature of some of the questions. It also discusses some of the strategies the service provider used to address these concerns and be able to utilize the tool in a culturally effective manner.